Implantable cardioverter defibrillator infection due to Mycobacterium mageritense. Issue 3 (March 2016) - Fukunaga, Masato; Goya, Masahiko; Ogawa, Midori; Fukuda, Kazumasa; Taniguchi, Hatsumi; Ando, Kenji; Iwabuchi, Masashi; Miyazaki, Hiroaki
Abstract: Rapidly growing non-tuberculous mycobacteria (RGM) are usually detected in blood cultures after 4–5 days of incubation, so it is important to differentiate RGM from contamination of commensal organisms on human skin. We report an unusual case of Mycobacterium mageritense bacteremia and infection of an implantable cardioverter defibrillator originally misidentified as Corynebacterium spp. or Nocardia spp. in gram-stained smears. 16S rRNA gene sequencing had utility in the definitive identification of isolates. We should be aware that RGM infection may exist in repeated implantable device infections.